PECULIARITIES OF FOREIGN STUDENTS TRAINING TO UKRAINIAN DIALOGUE COMMUNICATION IN HIGHER SCHOOL BY MEANS OF INFORMATION TECHNOLOGIES - Drozdova, I. P.; Savchak, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article defines the conceptual principles of information technologies integration into the education process in order to form Ukrainian-speaking professional competence for teaching dialogue. The professional training of foreign students by means of information technology involves the specifics of learning, organizing the student’s educational and cognitive activities, and developing interest in education and profession. The role and importance of positive motivation which stimulates the development of a favorable psychological climate for foreign students’ dialogue communication in the Ukrainian language within the professional communication is outlined. The professional training of foreign students determines the communicative orientation and informationally-metho-dological support of Ukrainian-language dialogical speech study. It is stated that the communicative orientation of learning is always a speech aimed activity which promotes students’ creative self-expression (role plays, discussions, presentations, "brainstorming"). The information and metho-dological support includes curricula and programs, methodological recommendations to them, scientific manuals, information and reference materials and other teaching materials. It is noted that the development of student’s information culture improves foreign students’ abilities, helps to meet their inquiries and needs, and reveal creative potential in the process of their professional growth. Multimedia technology is the basis of interactive student learning. Due to multimedia system application, complex skills of Ukrainian dialogue communication are being improved.